Strength and conditioning for golf - Hennessy, L. (Strength and conditioning for sports performance, 2016)
In recent years, the sport of golf has been revolutionised. The revolution perhaps started long before the appearance of Tiger Woods when legendary golfers such as Gary Player complemented their technical practice with physical fitness routines. While the word about the impact of physical fitness on their golfing performance did not spread far and wide, the appearance of Tiger Woods in 1996 forced the world to rethink how to build and develop a golfer. Joining Tiger Woods in the quest for better golf efficiency, proficiency and performance is a growing band of exceptional golfers. They typically display certain physical characteristics that allow them to achieve greater driver carry distance, greater ball speed, greater consistency and ultimately greater performance. So is there scientific evidence to show that top goiters indeed are different to, shall we say, the mere mortal golfer?